1991
DOI: 10.1093/jac/27.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of virulence factors of Pseudomonas aeruginosa by erythromycin

Abstract: The effects of erythromycin stearate over a concentration range of 0.1-10 mg/l on production of elastase, protease and leucocidin by clinical isolates of Pseudomonas aeruginosa were investigated. Growth of P. aeruginosa N42 in broth was not affected significantly during 24 h culture with erythromycin (0.1-10 mg/l), although extracellular protein contents were reduced by erythromycin at concentrations of 0.1-1.0 mg/l. Production of elastase and protease by strain N42 was significantly suppressed by erythromycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 0 publications
2
45
0
Order By: Relevance
“…This was an unexpected finding, considering the high levels of resistance that P. aeruginosa shows toward these drugs, and general anti-inflammatory effects associated with macrolides were suggested to account for the positive results (312). However, in vitro testing with subinhibitory concentrations of macrolides indicated an additional effect of their application on reduction of P. aeruginosa virulence factor expression, including decreased production of exotoxin A, proteases, elastase, DNase, leukocidin, and phospholipase C (313)(314)(315). Positive outcomes from sub-MIC AZM treatments against P. aeruginosa in a murine pneumonia model provided further laboratory evidence that macrolides could affect the physiology of the bacteria without inhibiting their growth in vivo (316).…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 98%
“…This was an unexpected finding, considering the high levels of resistance that P. aeruginosa shows toward these drugs, and general anti-inflammatory effects associated with macrolides were suggested to account for the positive results (312). However, in vitro testing with subinhibitory concentrations of macrolides indicated an additional effect of their application on reduction of P. aeruginosa virulence factor expression, including decreased production of exotoxin A, proteases, elastase, DNase, leukocidin, and phospholipase C (313)(314)(315). Positive outcomes from sub-MIC AZM treatments against P. aeruginosa in a murine pneumonia model provided further laboratory evidence that macrolides could affect the physiology of the bacteria without inhibiting their growth in vivo (316).…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 98%
“…However, preincubation of neutrophils alone with erythromycin was without effect, suggesting that erythromycin might reduce P. aeruginosa's production of factors that damage epithelia or stimulate neutrophilmediated cytotoxicity. At sub-MIC levels, macrolides inhibit the synthesis of exotoxin A, elastase, phospholipase C, DNase, lecithinase, gelatinase, lipase, and pyocyanin, all of which are virulence factors associated with P. aeruginosa infection (89,143,193,195,266). Tateda and coworkers (297) showed that a 48-hour exposure to macrolides at sub-MIC levels decreased the viability of both mucoid and nonmucoid P. aeruginosa strains.…”
Section: Inhibition Of Virulence Factorsmentioning
confidence: 99%
“…It has recently been reported that treatment with erythromycin (EM) improves the clinical symptoms and prognosis of patients with chronic pulmonary infections (18). Kita et al (18) have shown that erythromycin stearate (EMS) suppresses the production of protease and leukocidin by P. aeruginosa without affecting cell growth and speculated that EMS may affect the virulence factors of this organism (18) and host defense mechanisms (7,9,17).…”
mentioning
confidence: 99%